O26 Testing an intervention to reduce fatigue impact in inflammatory arthritis: design and outcomes of a single-arm feasibility study. (26th April 2021) - Bridgewater, Susan; Lomax, Joe; Abbott, Bryan; Adams, Jo; Berry, Alice; Creanor, Siobhan; Ewings, Paul; Hewlett, Sarah; McCracken, Lance; Ndosi, Mwidimi; Thorn, Joanna; Urban, Marie; et al.
Abstract: Background/Aims   Patients with inflammatory arthritis report that fatigue can be a challenging symptom to manage, with little support available. In response, we developed a brief one-to-one cognitive-behavioural manualised intervention, delivered by rheumatology health professionals (RHPs), to help patients manage their fatigue. Methods   We designed a single-arm feasibility study called FREE-IA (Fatigue - Reducing its Effects through individualised support Episodes in Inflammatory Arthritis). Patients were eligible if they were ≥18 years, had a clinician confirmed diagnosis of inflammatory arthritis, scored ≥6/10 on the BRAF NRS Fatigue Impact with fatigue that they considered recurrent, frequent, and/or persistent, and were not accessing support for their fatigue. Following training, RHPs delivered 2-4 one-to-one sessions to participants. The initial two core sessions were delivered face-to-face in clinic; participants then had the option of up to two further sessions, either in clinic, by telephone or online. We proposed delivering sessions 1 and 2 within two weeks of each other, and sessions 3 and 4 in the following two weeks. Baseline data were collected before the first session (T0), and outcomes at six weeks (T1) and six months (T2). The primary outcome was fatigue impact (BRAF NRS Fatigue Effect), collected by telephone. Secondary outcomes included fatigue severity, fatigue coping, multi-dimensional impact of fatigue, disease impact and disability and measures of therapeutic mechanism (self-efficacy, and perceived confidence and autonomy to manage health). These outcomes were collected by post. This study allowed us to test the feasibility and acceptability of RHP training, study design and materials, intervention delivery and outcome collection, ahead of a possible RCT to determine intervention effectiveness. Results   Eight RHPs at five hospitals delivered 113 sessions to 46 participants. Four sessions were delivered by phone and none online. Session 2 was only delivered within the two-week time frame for 37% of participants attending both core sessions. Out of a potential 138 primary and secondary outcome responses at T0, T1 and T2, there were 13 missing primary outcome responses and 27 missing secondary outcome responses. Results indicated improvements in all measures except disability at either T1 or T2, or both, with confidence intervals supporting an interpretation of improvement. Conclusion   We were able to design and deliver FREE-IA training to RHPs, deliver FREE-IA sessions to patients, and collect outcomes at three time points with low levels of attrition. Outcomes in all measures except disability were in a direction to suggest improvement at T1, T2, or both. Study numbers were small, there was no control group and regression to the mean was a possibility. However, outcomes were in the direction to cautiously suggest benefit, and there is evidence of promise of the intervention. A definitive RCT is the next step to test clinical and cost effectiveness of the intervention. Disclosure   S. Bridgewater: None. J. Lomax: None. B. Abbott: None. J. Adams: None. A. Berry: None. S. Creanor: None. P. Ewings: None. S. Hewlett: None. L. McCracken: None. M. Ndosi: None. J. Thorn: None. M. Urban: None. E. Dures: None.